A conscientious approach to claims management strategies in international projects using fidic based contracts - Sevin, Özlem. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
The management of construction claims is the greatest challenge that is facing contractors in today’s competitive business environment. Construction projects are becoming increasingly susceptible to a variety of factors that give rise to time extensions and cost recovery. Although the construction business environment has moved toward partnering arrangements in recent years, the number of contractual difficulties continues to rise. Thus the construction industry needs to develop methodologies for construction claim management to better manage the on going trend. Realizing the importance of this need, this study aims to provide an overview for construction claims management. The thesis opens with a discussion on whether the discords can be solved as potential change orders before escalating into major problems and becoming claims. Then, accepting the fact that changes take place in every project, in order to understand the nature of claims before dealing with them, the clauses that trigger claims in FIDIC’s Fourth Edition (or General Conditions of Contract for Civil Engineering Works) are investigated. Ten major clauses are chosen to consider the more significant problems experienced by contractors. Different views are presented in order to give the reader an essence of what the basis of the claim for the chosen clause is. The validity of these commentaries is then tested using real time case studies. The last section of the study provides the fundamentals for claims management. The records to be kept at different stages of the project are described and the important points to be considered during the preparation of a well documented claim are provided.
Keywords: Project management.; Claims.